Coping with COVID in corrections: a qualitative study among the recently incarcerated on infection control and the acceptability of wastewater-based surveillance - Lindsey R. Riback; Peter Dickson; Keyanna Ralph; Lindsay B. Saber; Rachel Devine; Lindsay A. Pett; Alyssa J. Clausen; Jacob A. Pluznik; Chava J. Bowden; Jennifer C. Sarrett; Alysse G. Wurcel; Victoria L. Phillips; et al. (BMC, 2023)
Abstract Background Correctional settings are hotspots for SARS-CoV-2 transmission. Social and biological risk factors contribute to higher rates of COVID-19 morbidity and mortality among justice-involved individuals. Rapidly identifying new cases in congregate settings is essential to promote proper isolation and quarantine. We sought perspectives of individuals incarcerated during COVID-19 on how to improve carceral infection control and their perspectives on acceptability of wastewater-based surveillance (WBS) accompanying individual testing. Methods We conducted semi-structured interviews with 20 adults who self-reported being incarcerated throughout the United States between March 2020 and May 2021. We asked participants about facility enforcement of the Centers for Disease Control and Prevention (CDC) COVID-19 guidelines, and acceptability of integrating WBS into SARS-CoV-2 monitoring strategies at their most recent facility. We used descriptive statistics to characterize the study sample and report on acceptability of WBS. We analyzed qualitative data thematically using an iterative process. Results Participants were predominantly Black or multiple races (50%) and men (75%); 46 years old on average. Most received a mask during their most recent incarceration (90%), although only 40% received counseling on proper mask wearing. A quarter of participants were tested for SARS-CoV-2 at intake. Most (70%) believed they were exposed to the virus while incarcerated. Reoccurring themes included (1) Correctional facility environment leading to a sense of insecurity, (2) Perceptions that punitive conditions in correctional settings were exacerbated by the pandemic; (3) Importance of peers as a source of information about mitigation measures; (4) Perceptions that the safety of correctional environments differed from that of the community during the pandemic; and (5) WBS as a logical strategy, with most (68%) believing WBS would work in the last correctional facility they were in, and 79% preferred monitoring SARS-CoV-2 levels through WBS rather than relying on just individual testing. Conclusion Participants supported routine WBS to monitor for SARS-CoV-2. Integrating WBS into existing surveillance strategies at correctional facilities may minimize the impact of future COVID-19 outbreaks while conserving already constrained resources. To enhance the perception and reality that correctional systems are maximizing mitigation, future measures might include focusing on closer adherence to CDC recommendations and clarity about disease pathogenesis with residents.